The mitochondrial genome of the black-tailed dusky antechinus (Antechinus arktos). Issue 4 (1st October 2020) - Geng, Yuepan; Yang, Chen; Guo, Han; Thomas, Patrick B.; Jeffery, Penny L.; Chopin, Lisa K.; Baker, Andrew M.; Tian, Ran; Seim, Inge
Abstract: In this study, we report the mitochondrial genome of the black-tailed antechinus ( Antechinus arktos ), a recently-discovered, endangered carnivorous marsupial inhabiting a caldera that straddles the border of Australia's mid-east coast. The circular A. arktos genome is 17, 334 bp in length and has an AT content of 63.3%. Its gene content and arrangement are consistent with reported marsupial mitogenome assemblies.